FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELAJAR SISWA DALAM MATA PELAJARAN IPS DIKELAS VII 1 SMP PERTIWI SITEBA PADANG TAHUN PELAJARAN 2013/ 2014 - Wati, Eli Puteri; Nazmi, Ranti; Meldawati, Meldawati (Pendidikan Sejarah, 2014)
This research is motivated by the problem of poor student interest in social studies in junior high school Pertiwi Siteba Padang. On the basis of the problem of this research focuses on the factors that affect student interest in social studies class VII SMP Pertiwi Siteba Padang I Semester Academic Year 2013/2014. Study aimed to describe the factors that affect student interest in class VII I Padang SMP Pertiwi Siteba Padang Academic Year 2013/2014, views of the motivations and ideals, the family, the role of teachers, facilities and infrastructure, friend relationships, and mass media. Based on these problems, the method used in this study is the evaluation study. To test the validity of the data the authors used data triangulation. Then the techniques of data analysis in this study using the interactive analysis technique proposed by Huberman Milles.The results showed: the interest of students seen from motivation and ideals associated with serious social studies so that students in learning. Family at home giving attention and some are not considered thereby reducing student interest in social studies. The role of teachers in students interest is very significant, because the teacher is a person who is responsible for the learning process of students. Facilities and infrastructure available in schools to increase interest seen from the availability of books and other state facilities which are in good condition to enhance students interest in learning. Mass media influence on students interest because students. Students have good relationships with friends at school. This increase students interest in learning as socially friends can help when students have difficulties in learning. From the above description be concluded poor student interest in social studies at the high school following the Pertiwi Siteba Padang.